CUSTODIAM PRAESTARE - EWOLUCJA ZOBOWIĄZANIA DO STRZEŻENIA RZECZY W PRAWIE RZYMSKIM - Kordasiewicz, Stanisław (Zeszyty Prawnicze, 2017)
‘Custodiam praestare’ - The Evolution of an Obligation to Guarantee the Safekeeping of an Object in the Roman Law Summary This article focuses on the evolution of an obligation to guarantee the safekeeping o f an object (custodiam praestare). This kind of a duty arose in all contracts in which the debtor received things for his own interest. The limits of liability were discussed by the earlier jurists (veteres) in the contract of loan for use (commodatum). In the first analyzed text (D. 13,6,5,6) the problem concerned the necessity of safekeeping of a slave loaned for use; the second case (D. 13,6,5,9) discussed the duty of safekeeping of a thing accompanying the main object of a contract. The argumentation adopted by the veteres proves that already for the early jurists the very obligation to keep safe o f an object in commodatum was unquestionable: they were rather to decide arising troublesome controversies. The meaning of custodiam praestare as an obligation to guarantee the safekeeping of an object and the problem when such an obligation arose was analyzed by Gaius in his commentary to the provincial edict (D. 19,2,40 and D. 4,9,5 pr.). The jurist laid down that the duty to keep an object safe is not a principal obligation in agreements contracted with the seamen, inn- and stable-keepers, they were liable for the safekeeping in the same way as fullers and tailors. The obligation custodiam praestare in case of fullo and sarcinator was clarified in Gaius’ Institutiones (G. 3,205 -207): a party was liable for safekeeping of an object, when it received the object for its own interest. Custodiam praestare evolved by way of an interpretation o f the term custodia. The first concept of liability for safekeeping of an object was restricted to theft (D. 13,6,19) and it did not include damage induced by a third party. Subsequently, Marcellus introduced a wider interpretation of safekeeping: a party would be liable for not returning the object kept, as long as the activity of custodia would have been enough to avoid an unlawful damage (D. 19,2,41). This understanding broadened the limits of liability: eventually, towards the end of the classical period custodia apparently covered every loss but for the case of force majeure (D. 13,7,13,1). In the postclassical period there seems to have occurred a change in the regime of custodia liability. M any a text brings a new formulation: instead of custodiam praestare we find the expression diligentia in custodiendo, thus one could think that this kind of liability was then based on negligence. Nevertheless, this terminological alteration did not affect the limits of liability. The person under the obligation to keep an object safe remained liable for the loss thereof and could only be exonerated by proving that the loss was due to vis maior (D. 18,6,2,1).